Visions of sharīʻa : contemporary discussions in Shi'i legal theory - Bhojani, Ali Reza; De Rooij, Laurens; Bohlander, Michael, 1962- (Nordrhein-Westfälische Akademie der Wissenschaften und der Künste - Abhandlungen beider Klassen, 2020)
In Visions of Sharīʿa Bhojani, De Rooij and Bohlander present the first broad examination of ways in which legal theory ( uṣūl al-fiqh ) within Twelver Shīʿī thought continues to be a forum for vibrant debates regarding the assumptions, epistemology and hermeneutics of Sharīʿa in contemporary Shīʿī thought. Bringing together authoritative voices and emerging scholars, from both 'traditional' seminaries and 'Western' academies, the distinct critical insider and emic accounts provided develop a novel avenue in Islamic legal studies. Contextualised through reference to the history of Shīʿī legal theory as well as contemporary juristic practice and socio-political considerations, the volume demonstrates how one of the most intellectually vibrant and developed discourses of Islamic thought continues to be a key forum for exploring visions of Sharīʿa .